2020
DOI: 10.1177/1073274820931808
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Changes Associated With Ibrutinib Exposure

Abstract: Although ibrutinib-associated atrial and ventricular arrhythmias have been well described, there is little information about ibrutinib’s effects on other electrocardiographic parameters, particularly the QT interval. Using our database of 137 patients treated with ibrutinib, we retrospectively identified 21 patients in whom an electrocardiogram (ECG) was obtained both prior to and after ibrutinib exposure. All traditional ECG parameters as well as QT dispersion were manually measured by an electrophysiologist.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“… 26 However, in another study, Fradley et al retrospectively analyzed 137 patients and found that the incidence of short QT intervals tended to increase after ibrutinib exposure. 59 Furthermore, a sequential administration of single doses of therapeutic and super-therapeutic concentrations of ibrutinib revealed that ibrutinib shortened the QTc interval and prolonged the PR interval, which was consistent to the results from the Phase 1b/2 study 1102. 72 In conclusion, QT interval change is not strongly correlated with ibrutinib-induced cardiotoxicity.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“… 26 However, in another study, Fradley et al retrospectively analyzed 137 patients and found that the incidence of short QT intervals tended to increase after ibrutinib exposure. 59 Furthermore, a sequential administration of single doses of therapeutic and super-therapeutic concentrations of ibrutinib revealed that ibrutinib shortened the QTc interval and prolonged the PR interval, which was consistent to the results from the Phase 1b/2 study 1102. 72 In conclusion, QT interval change is not strongly correlated with ibrutinib-induced cardiotoxicity.…”
Section: Introductionsupporting
confidence: 82%
“…A retrospective study that quantified the incidence rates and risk of AA in 137 patients treated with ibrutinib and in 106 patients diagnosed with B cell malignancies and treated with chemotherapy confirmed that the use of ibrutinib is an independent risk factor for the incidence of AA. 59 Ibrutinib use was also associated with a 5.2-fold increased risk of AA development, 14% in the ibrutinib-treated group versus 3% in the chemotherapy group.…”
Section: Introductionmentioning
confidence: 95%
“…23,58 In fact, ibrutinib may shorten the QT interval, with enhanced automaticity and triggered activity suggested as mechanisms for arrhythmogenesis. 24,25,59,60…”
Section: Ventricular Arrhythmiasmentioning
confidence: 99%
“…Fradley et al enrolled 137 patients who were treated with ibrutinib, 21 pre-and post-ibrutinib ECG readings were obtained. Compared with the pre ibrutinib ECG, after administration, the ECG showed QT interval shortening from 446 to 437 ms, based on Bazett's formula (47). In another phase II clinical trial, a mean 7.5 ms shortening of the corrected QT interval was found after ibrutinib treatment (34).…”
Section: Ibrutinibmentioning
confidence: 99%